2004
DOI: 10.1023/b:viru.0000032790.16751.13
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Sheep Pox and Goat Poxviruses by Sequence Analysis and PCR-RFLP of P32 Gene

Abstract: Sheep pox and Goat pox are highly contagious viral diseases of small ruminants. These diseases were earlier thought to be caused by a single species of virus, as they are serologically indistinguishable. P32, one of the major immunogenic genes of Capripoxvirus, was isolated and Sequenced from two Indian isolates of goat poxvirus (GPV) and a vaccine strain of sheep poxvirus (SPV). The sequences were compared with other P32 sequences of capripoxviruses available in the database. Sequence analysis revealed that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
62
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 16 publications
10
62
1
Order By: Relevance
“…The GTPVs, and to a lesser extent the LSDV, lineages show more diversity than in the SPPV group. This observation was also observed previously for the P32 gene, but using a very limited number of isolates (Hosamani et al, 2004). Our GTPVs fall into three subgroups.…”
Section: Analysis Of Capripoxvirus Gpcr Genesupporting
confidence: 67%
See 4 more Smart Citations
“…The GTPVs, and to a lesser extent the LSDV, lineages show more diversity than in the SPPV group. This observation was also observed previously for the P32 gene, but using a very limited number of isolates (Hosamani et al, 2004). Our GTPVs fall into three subgroups.…”
Section: Analysis Of Capripoxvirus Gpcr Genesupporting
confidence: 67%
“…This study shows that GTPV and LSDV are more closely related to each other than to SPPV. This would support the hypothesis that they both emerged from a common ancestor close to the SPPVs, as proposed by others who carried out phylogenetic studies on different genome segments (Hosamani et al, 2004;Stram et al, 2008). This assumption is, however, in contradiction with another study, which concluded that small ruminant poxviruses may have emerged from a common LSDV-like ancestor, based on the observation in GTPV and SPPV of disrupted LSDV genes with putative virulence and host range functions (Tulman et al, 2002).…”
Section: Analysis Of Capripoxvirus Gpcr Genecontrasting
confidence: 54%
See 3 more Smart Citations